Modulating Role of Breastfeeding Toward Long COVID Occurrence in Children: A Preliminary Study - Vizzari, Giulia; Morniroli, Daniela; Tiraferri, Valentina; Castaldi, Silvana; Patria, Maria Francesca; Marchisio, Paola; Agostoni, Carlo; Mosca, Fabio; Buonsenso, Danilo; Milani, Gregorio Paolo; Giannì, Maria Lorella; , The CHICO Study Group; et al. (Frontiers in Pediatrics, 2022)
The SARS-CoV-2 (Severe acute respiratory syndrome Coronavirus-2) pandemic has forced the global health system to face new challenges both in the acute management of COVID-19 (Coronavirus Disease 2019) patients and in its consequences. In particular, the long-term effects of this new virus, especially in children, are still poorly understood. Scientific research is currently trying to understand the mechanisms underlying the so called “long COVID syndrome”. Since the beginning of the pandemic, breastmilk has been studied for its antiviral and immunomodulatory properties. Based on these assumptions, we conducted a preliminary study in order to investigate the prevalence of long COVID in a cohort of Italian children with previously detected SARS-CoV-2 infection and evaluate if breastfeeding might play a role in modulating long COVID occurrence.